Trends Of Antibiotic Susceptibility Of Salmonella Enterica Serovar Typhi And Paratyphi In An Urban Hospital Of Dhaka City Over 6 Years Period - Shadia, Khandaker; Borhan, Shajeda Binte; Hasin, Humaira; Rahman, Sharmin; Sultana, Shahin; Barai, Lovely; Jilani, MS Alam; Haq, J Ashraful (Ibrahim Medical College Journal, 2012)
The antibiotic resistance pattern of salmonella is ever changing over time. The present study is a retrospective analysis of rate of isolation of Salmonella Typhi and Paratyphi and their antibiotic resistance pattern over 6 years period in an urban hospital of Dhaka city. Blood culture submitted in BIRDEM hospital from 2004-2009 were analyzed. Isolated Salmonella sp were identified and antimicrobial susceptibility testing was carried out by a standard disc diffusion method. Among 385 isolated Salmonella sp 304 (79%) were Salmonella enterica serovar Typhi and 81 (21%) were Salmonella enterica serover Paratyphi A. The rate of isolation of S. Paratyphi A has increased over 6 the year period from 14% to 24%. Resistance to individual first line anti-salmonella drugs has increased from 2004 to 2006 (42 to 63%) but has decreased thereafter. Similar pattern was found when simultaneous resistance to three first line antibiotics namely ampicillin, chloramphenicol and co-trimoxazole were considered. Out of total 304 S. Typhi, 117 (38%) were simultaneously resistant to all three first line drugs compared to only 1.8% S. Paratyphi A. Analysis showed that 80 to 90% of isolated S. Typhi was nalidixic acid resistant (NARST) with reduced susceptibility to ciprofloxacin while the rate for S. Paratyphi A was 71-94%. All S. Typhi and Paratyphi A were sensitive to ceftriaxone. The study showed that there was a gradual decline of resistance of S. Typhi to first line antibiotics but very high prevalence of nalidixic acid resistant S. Typhi and S. Paratyphi in Bangladesh. DOI: http://dx.doi.org/10.3329/imcj.v5i2.10097 IMCJ 2011; 5(2): 42-45